Penerapan Asas Proporsionalitas Dalam Perjanjian Waralaba (Franchise) Pada Suatu Hubungan Kontrak Bisnis - Dwi Atmoko (Jurnal Hukum Sasana, 2022)
In essence, a franchise business is a form of business that markets goods or services that have certain characteristics in their activities. Franchise activity itself in Indonesia is regulated in the Regulation of the Minister of Trade Number 71 of 2019 concerning the Implementation of Franchising. A franchise agreement entered into by both parties entering into an agreement in a business contract must be based on good faith and based on the principle of proportionality, in the sense that the agreement provides sense of fairness with the aim of providing benefits for both parties in running the franchise business. A business contract runs on the principle of good proportionality, of course, it begins with a valid legal agreement as regulated in the Civil Code (KUHPer) which regulates the legal requirements of an agreement in Article 1320. Several clauses in a contractual agreement related to franchising, especially for risky clauses, should be a top priority, related to the profit and term of use of the franchise. Talks and discussions that marked a good start in the draft franchise contract design, of course, will produce a good contract as well. In addition, by designing a good and correct contract in the franchise business, of course, it will avoid disputes or legal disputes for both parties in the future.